Evaluating the Quality of 2G and 4G Networks on Telkomsel in Gunung Talang and Danau Kembar Sub-Districts - Rifatun Nissa; Dikky Chandra; Siska Aulia; Adinda Aliya Maharani (International Journal of Wireless And Multimedia Communications, 2025)
This study aims to evaluate the quality of 2G and 4G networks on Telkomsel operators in Gunung Talang District and Danau Kembar District, Solok Regency, West Sumatra. This research was conducted using the drive test method using TEMS Pocket and TEMS Discovery devices for network data collection and analysis. The 2G network measurements were conducted based on Rx Level and Rx Quality parameters. In contrast, the 4G network was evaluated based on RSRP (Reference Signal Receive Power) and SINR (Signal Interference to Noise Ratio) parameters. The measurement results on the 2G network show that the average Rx Level is at -85.1 dBm, with very poor signal quality reaching 27.14%, while the network quality based on Rx Quality is classified as excellent with an average value of 0.9 dB, which reaches 82.21%. On the 4G network, the average RSRP was -101.7 dBm with a good signal dominance of 30.68%, but the network quality based on SINR was lower, with an average value of 12.3 dB, where 46.98% of the signal was classified as fair. In addition, several bad spot areas were found to be affected by natural obstacles such as hills, cliffs, and tall trees that block the signal. The recommendation from this research is to optimize the nearest site to improve signal quality in these areas, especially to reduce overshooting problems that occur in certain sectors. This research is expected to be a reference for operators in improving network quality in the areas studied